Salinity Stress and Varietal Resistance in Rice: Effects on Whitebacked Planthopper - Salim, M.; Saxena, R.C.; Akbar, M. (Wiley, 1990)
Plants grown under physicochemical stresses frequently become more susceptible to insects. We determined the effects of salinity stress at 1.0 and 1.2 S/m electrical conductivity on the magnitude and expression of resistance of rice (Oryza sativa L.) cultivars to Sogatella furcifera (Horváth) under glasshouse conditions using natural daylight of 12 h, 29/21 °C (day/night), and minimum 70% relative humidity. Salinity stress increased N, decreased K, and decreased the quantity of allelochemicals extracted as steam distillates from rice plants. Intake and assimilation of food, growth, adult longevity, fecundity, and population increase of the insect were significantly greater on plants grown at salinity level of 1.2 S/m than on unstressed control plants. Regardless of the level of stress, the difference between susceptibility of ‘Taichung Native 1’ (TN1) and resistance of ‘IR2035‐117‐3’ (IR2035) cultivars remained distinct. Painting of steam‐distillate extract of resistant IR2035 plants on susceptible TN1 plants made them less attractive and decreased food intake and assimilation by S. furcifera. In contrast, intake and assimilation of food increased significantly on IR2035 plants painted with TN1 extract. Effects of Physicochemical stresses, such as salinity, must be considered when breeding insect‐resistant rice cultivars for salinity‐prone areas.